Implementation of video learning media in Islamic Religious Education subjects - Anggraeni, Risma; Maryanti, Rina (Indonesian Journal of Multidiciplinary Research, 2021)
The development of technology in the world of education brings various positive and negative impacts. In this regard, the use of technology in learning in the modern era has led to various kinds of innovations, which are marked by the use of video as a learning medium. This study aims to explore the video-based learning process as a learning medium, as well as to analyze teacher and student perceptions of these activities. This study used a qualitative descriptive approach with three data collection techniques, namely interviews, observation, and documentation. Based on this, the researchers found findings in the form of, the application of video as a learning medium received a good response from teachers and students, one of which was an interesting activity because in addition to being educational. In addition, the results showed that with the use of video as a learning medium, students became more focused and enthusiastic, but in this use, it was found that students were not very comfortable due to problems in several ways, one of which was the low quality of the video causing audio and visual elements of the material. Islamic Religious Education Learning is not delivered optimally.